Beyond Humanity: Quo Vadis the Politics of Robot Citizenship - Haikal Fadhil Anam (Universitas Negeri Surabaya, 2025)
This research explores the evolving concept of citizenship in the age of artificial intelligence and robotics. With the increasing integration of autonomous robots into society, traditional notions of membership, legal status, rights, and civic participation are being reexamined. The study focuses on the legal and ethical challenges of recognizing robots as citizens, using frameworks such as Stokke's four dimensions of citizenship: membership, legal status, rights, and participation. By analyzing current discourse on humanoid robots like Sophia, the research questions how, and under what conditions, robots could acquire citizenship. A qualitative approach is employed, drawing on various sources to critically assess the implications of robotic citizenship on societal structures, governance, and legal frameworks. The findings aim to contribute to the ongoing debate on the role of non-human entities in future societies, highlighting the need for comprehensive regulation and ethical considerations.